EFEKTIFITAS PENGGUNAAN MODUL KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN GURU PENDIDIKAN JASMANI (PENJAS) SEKOLAH DASAR - Purnamasari, Dyah Umiyarni; Ulfah, Nur; Kusnandar, Kusnandar (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2014)
ABSTRACT Measurement of nutritional status and physical fitness of school children in the District of South Purwokerto not be interpreted as the complete data and performed routinely. This study aims to increase knowledge of physical education teachers  through the provision of health module. The research method using a Quasi Experiment with design One Group Pre-Test and Post-Test. Test data analysis using Paired T-Test. The results showed differences in the results of the p-value = 0.000 <?: 0.05, thus indicating no significant differences in health knowledge through the media module to change the average score of knowledge that is 22.05. Suggestion to apply  their  knowledge for the measurement of nutritional status and physical fitness routine in the students so that the data obtained can be used to plan health interventions in school children. Key words : modul, nutritional status, physical fitness  Kesmasindo, Volume 6,  (3) Januari 2014, Hal. 176-182